Comparison of retrospective and prospective memory in subtypes of obsessive-compulsive disorder - Mohammad Taghi Yazarloo; Mehdi Reza Sarafraz; Saeide Jabbari; Taraneh Gholipour; Touraj Hashemi (PAGEPress Publications, 2024)
Retrospective and prospective memory deficits play a role in maintaining and perpetuating the symptoms of obsessive-compulsive disorder (OCD), but less is known about these deficits in different subtypes of OCD. The aim of the present study was to evaluate the retrospective and prospective memory in patients suffering from cleaning, checking, symmetry, and religious obsessions. In a comparative causal method, 60 participants aged 28 to 55, in 2023, were selected by convenience sampling and placed in five groups of individuals with cleaning, checking, symmetry, religious obsessions, and a healthy group. Participants completed self-report questionnaires and neurocognitive tools. Results showed that defects in retrospective memory were significant in all types of obsessions (p<0.05) except religious obsessions. Also, this defect was more severe in checking obsession disorder compared to other types of OCD. Also, the finding indicated that the defect in prospective memory was significant only in checking obsession disorder (p<0.05). Retrospective and prospective memory impairments and their relationship with deficits in executive functions can be different depending on the type of OCD. Based on the findings, impairment of executive function indirectly by impacting the impairment of other cognitive mechanisms diminishes confidence in retrospective and prospective memory which leads to compulsive behaviors in individuals with contamination and checking obsessions. Also, the impairment of retrospective memory in symmetry obsessions might have a relationship with information encoding, which in turn leads to difficulty recalling information from memory.